Reverse Microemulsion of Igepal CO-720 System as Microreactor For CdS Synthesis - Fitria Rahmawati; Indah Rizki Fitriani; Abu Masykur (UNIVERSITAS SEBELAS MARET (UNS), 2014)
A Research on CdS synthesis in reverse microemulsion of Igepal CO-720 system has been conducted at various weight ratio of water to surfactant. Igepal CO-720 naturally forms oil in water (o/w) emulsion type due to its high HLB (Hydrophilic -Lipophilic Balance) value. Therefore, in this research the Igepal CO-720 system was inversed into water in oil (w/o) system before it was used as microreactor for CdS synthesis. As comparison, a system of AOT (Aerosol OT; sodium bis (2-ethylhexyl) sulfosuccinate) which is naturally w/o system was also used as microreactor for CdS synthesis. The prepared CdS was analyzed by X-ray diffraction for crystal identification, scanning electron microscope for morphological analysis, UV-Vis for absorption edge determination and photoelectrochemical testing for photoactivity. The results show that the Igepal CO -720 system can be inverted into w/o system and can be used as microreactor for CdS synthesis. The prepared CdS is in nanosize with the average diameter of 2.517 ± 0.014 nm and the average gap energy of 3.805 ± 0.178 eV. The prepared CdS in Igepal CO-720 system has less regular form in comparison with morphology of the prepared CdS in AOT system. As the ω values decreases the particle diameter decreases, the gap energy increases and the % IPCE increases. It indicates that high surfactant concentration allows small size micelles formation and produced smaller CdS particle that has high surface area and therefore provide higher photocatalytic activity which was indicated by high value of its % IPCE.